A longitudinal analysis of school discipline events among youth in foster care. (October 2018) - Kothari, Brianne H.; Godlewski, Bethany; McBeath, Bowen; McGee, Marjorie; Waid, Jeff; Lipscomb, Shannon; Bank, Lew
Abstract: Youth in foster care experience major deficits on standardized measures of academic functioning, are at high risk of academic failure, and are more likely than their non-foster peers to be disciplined at school. School discipline-related problems increase risk of problematic educational and behavioral outcomes including dropping out of school, repeating a grade, and engagement in delinquent and criminal behavior. Identifying which youth are at greatest risk for experiencing school discipline is needed in order to improve the educational experiences of youth in foster care. The current investigation examined the effects of youth and contextual characteristics on school discipline events among 315 youth in foster care. Results revealed that being male, in a higher-grade, and a student of color, living apart from one's sibling, and school mobility significantly predicted discipline events. An additional statistical model divided youth into groups based on race, sex, and disability status taking into account the multiple identities youth have. These results suggest that gender, race, and disability status cumulatively inform school discipline experienced among youth in foster care. Highlights: School discipline is assocated with both individual and contextual characteristics for youth in foster care. An intersectional approach indicated that gender, race and disability status cumulatively inform school discipline. Addressing school discipline care may be an important way to improve the educational wellbeing of foster youth.